2011
DOI: 10.1371/journal.pmed.1000423
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost Effectiveness of Expanding Harm Reduction and Antiretroviral Therapy in a Mixed HIV Epidemic: A Modeling Analysis for Ukraine

Abstract: A cost-effectiveness study by Sabina Alistar and colleagues evaluates the effectiveness and cost effectiveness of different levels of investment in methadone, ART, or both, in the mixed HIV epidemic in Ukraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 35 publications
6
138
0
Order By: Relevance
“…The number of PWIDs on OAT started growing substantially with the introduction of methadone maintenance treatment (MMT) in 2008. However, OAT coverage still remains inadequate to effectively decrease HIV transmission [36]. An increasing trend in PWID coverage with prevention services was reported in all study cities.…”
Section: Exposurementioning
confidence: 88%
“…The number of PWIDs on OAT started growing substantially with the introduction of methadone maintenance treatment (MMT) in 2008. However, OAT coverage still remains inadequate to effectively decrease HIV transmission [36]. An increasing trend in PWID coverage with prevention services was reported in all study cities.…”
Section: Exposurementioning
confidence: 88%
“…Meanwhile, evidence on the impact of MMT on health utility (preference-based HRQOL), an integral part of the quality-adjusted life years, is still very limited (Feeny, 2000). Moreover, in a systematic review of 22 economic evaluations of MMT, the author found no studies investigating the changes in healthcare service utilization and out-of-pocket (OOP) health expenditure in the presence of MMT (Alistar, Owens, & Brandeau, 2011;Barnett, 1999aBarnett, , 1999bBarnett & Hui, 2000;Barnett, Zaric, & Brandeau, 2001;Dijkgraaf et al, 2005;Doran, 2005;Doran et al, 2003;French, 2001;Hartz et al, 1999;Masson et al, 2004;Mojtabai & Zivin, 2003;Negrin & Vazquez-Polo, 2006;Shanahan et al, 2006;Sindelar, Olmstead, & Peirce, 2007;Tran et al, 2012bVanagas, Padaiga, & Bagdonas, 2010;Wammes et al, 2012;Warren et al, 2006;Xing et al, 2012;Zaric, Barnett, & Brandeau, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Because these two interventions may potentially compete for scarce resources, it is essential to determine the most cost-effective combination of these programs. We performed an analysis to determine the effectiveness and cost effectiveness of different levels and combinations of methadone and ART scale up [30]. We analyzed strategies that focus on increasing methadone slots, ART slots, or both.…”
Section: Harm Reduction and Hiv Treatment In Ukrainementioning
confidence: 99%
“…Because the HIV epidemic in Ukraine is representative of the HIV epidemic in Eastern Europe and Central Asia, these findings can inform HIV policy in Ukraine as well as in other countries in the region. To disseminate the results of this work, we published it in a widely read international medical journal [30]. We also translated the article into Russian for broader dissemination [31].…”
Section: Nonidusmentioning
confidence: 99%